Proposal of natural resources management focused on conservation and restoration in the lower section of Guadairilla river (Seville, Spain) - David Cristel Gómez Montblanch; Rafael Cámara Artigas (Boletín de la Asociación de Geógrafos Españoles)
This paper shows a proposal of management for the conservation and restoration of the lower basin of Guadarilla River, a tributary of Guadaíra (Guadalquivir basin). This is based on a methodology for natural resources management focused on the identification of environmental units under management from the analysis of geomorphological, hydrological and biogeographic elements and their changes along the time line. These changes produce areas of progression, stability or regression of the surface distribution of riparian plant communities that still remain in this river. A proposal of zoning based on the analysis of changes and the field knowledge about floristic and structural composition of riparian plant communities of Guadairilla River. This zoning is focused on three levels: management, conservation and restoration. The analysis shows the ability of environmental regeneration of thermo-mediterranean riverbanks when human pressure decreases and what would be the response of the environment to a land use planning designed with a sustainable criterion.